(untitled) (Singapore, 2003)
This volume contains the proceedings of the third meeting in the series of symposia and workshops on nuclear medium effects. The topics covered include many-body forces in few-nucleon systems, nuclear interactions in the medium, medium effects in nuclear reactions, properties of the nuclear medium, and related topics, with special emphasis on work related to experimental data with intermediate-energy light-ion projectiles.
Keywords: Nuclear physics,Many-body problem